2019
DOI: 10.1177/0042098019872391
|View full text |Cite
|
Sign up to set email alerts
|

Private government, property rights and uncertain neighbourhood externalities: Evidence from gated communities

Abstract: Economists traditionally view public and private land use regulation as alternatives to each other. An alternative view argues that public and private regulation are not equally suited to accomplish the same outcomes. In particular, government regulation is easily changed while private regulation is not, making the latter better suited to control future externality risk. One implication of the alternative view is that more risk-averse households are drawn to gated neighbourhoods while their less risk-averse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…They argued that deed restrictions and neighborhood restrictive covenants represent private land use contracts for reducing neighborhood externality risk. A further study along the same line is Turnbull and Zahirovic-Herbert (2020), who found that greater exogenous amenity uncertainty, as represented by public school attendance zone changes, yields stronger house price capitalization in gated subdivisions than in open neighborhoods. The reason is that in the USA, government regulation is easily changed while private regulation is not, making the latter better suited to control future externality risk.…”
Section: Literature Reviewmentioning
confidence: 93%
“…They argued that deed restrictions and neighborhood restrictive covenants represent private land use contracts for reducing neighborhood externality risk. A further study along the same line is Turnbull and Zahirovic-Herbert (2020), who found that greater exogenous amenity uncertainty, as represented by public school attendance zone changes, yields stronger house price capitalization in gated subdivisions than in open neighborhoods. The reason is that in the USA, government regulation is easily changed while private regulation is not, making the latter better suited to control future externality risk.…”
Section: Literature Reviewmentioning
confidence: 93%